A hermenêutica dos direitos fundamentais nas relações cooperativo-comunitárias - Conto, Mário de (Universidade do Vale do Rio dos Sinos, 2013)
The Cooperative Movement, as a product of modernity, arises in a historical moment whose denied the values of solidarity, focusing on the theory of an individual who, guided only the pursuit of their interests, should have their absolute freedom guaranteed by the state to thereby achieve its wellness. Such freedom preached by liberal ideology intensified the social question, in that freedom (especially as freedom of negotiation) in a context of gross material inequality became in a freedom to explore than an truly autonomy. The Modern Law was also constituted under this perspective: to allow ample freedom in relations between individuals, without any intervention of the State, unless the allocation of support such competition, regulating the relations of conflict between individuals in their conflicts interest. Contemporaneously, however , in a historical moment in which , under the paradigm of Democratic State of Law, solidarity is replaced central role as a way to overcome the inequalities bequeathed by the Liberal State - such feature state suffers transformation towards greater state intervention in this freedom - once unrestricted - individuals. The doctrinal discussions regarding such intervention whenever the assumption of a relationship of conflict between the parties , with diametrically opposed positions and usually in situations where one party has clear economic power over another, called "Power-Individuals". Accordingly, we seek to present the contribution of the notion of Cooperative-Community Relations for the unveiling of the phenomenon in the contemporary, to lay the foundation for the Efficiency of Fundamental Rights in such relationships, not a feature "semi-state" of such societies , nor in the recognition of an "Power-Individuals" Relations, but in recognition of Cooperative Societies as democratic societies , in which the observance of fundamental rights becomes his condiction.
Keywords: Crítica hermenêutica do direito; Direitos fundamentais; Cooperativas; Critical hermeneutics of law; Fundamental rights; Cooperatives; ACCNPQ::Ciências Sociais Aplicadas::Direito